2003
DOI: 10.1016/s0014-5793(03)00815-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphates strongly inhibit the tRNA dependent synthesis of poly(A) catalyzed by poly(A) polymerase from Saccharomyces cerevisiae

Abstract: Polyphosphates of di¡erent chain lengths (P 3 , P 4 , P 15 , P 35 ), (1 W WM) inhibited 10, 60, 90 and 100%, respectively, the primer (tRNA) dependent synthesis of poly(A) catalyzed poly(A) polymerase from Saccharomyces cerevisiae. The relative inhibition evoked by p 4 A and P 4 (1 W WM) was 40 and 60%, respectively, whereas 1 W WM Ap 4 A was not inhibitory. P 4 and P 15 were assayed as inhibitors of the enzyme in the presence of (a) saturating tRNA and variable concentrations of ATP and (b) saturating ATP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…We found that the presence of increased amounts of co-purified poly P in RNA preparations from Δpho85 and Δpho80 strains was accompanied by a strong inhibition of poly(A) polymerase activity. Consistent with our observations, previous biochemical work on the effects of poly P on yeast Pap1p revealed an inhibitory activity on tRNA primed poly(A) synthesis ( 56 ). We show in this work by filter-binding assays that poly P directly binds to yeast Pap1p with a k D in the low nanomolar range (0.38 nM).…”
Section: Discussionsupporting
confidence: 93%
“…We found that the presence of increased amounts of co-purified poly P in RNA preparations from Δpho85 and Δpho80 strains was accompanied by a strong inhibition of poly(A) polymerase activity. Consistent with our observations, previous biochemical work on the effects of poly P on yeast Pap1p revealed an inhibitory activity on tRNA primed poly(A) synthesis ( 56 ). We show in this work by filter-binding assays that poly P directly binds to yeast Pap1p with a k D in the low nanomolar range (0.38 nM).…”
Section: Discussionsupporting
confidence: 93%
“…Inorganic polyphosphates are probably present in every cell [17][18][19] and are particularly abundant in yeast extracts where P 3 and P 4 have been described at mM concentrations [17]. As previously pointed out [16], the potential effects carried out by polyphosphates (here P 3 and P 4 ) can be considered under two different aspects: either due their presence at high concentration and frequently condensed in organelles or due to their occurrence at low concentration in different cellular compartments. Although their role in the last case is not clear, there is a common concern about the possibility of polyphosphates playing more general and universal functions in biology [14,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 98%
“…In our experience, reaction (b) is rather unspecific and the AMP residue of the E-X-AMP complex (or E-AMP in some cases [3]) may react with the terminal phosphate of almost any molecule containing an intact terminal P-P-P, such as tripolyphosphate (P 3 ), tetrapolyphosphate (P 4 ), pentapolyphosphate (P 5 ) ATP, GTP, adenosine 5 0 -tetraphosphate (p 4 A), guanosine 5 0 -tetraphosphate (p 4 G), etc. In the case of luciferase, the moiety of AMP from E-luciferin-AMP can even be transferred to polyphosphates as long as linear-chain polyphosphates with an average chain length of 15 ± 3 (P 15 ) giving rise to a family of compounds as bizarre as p 16 A, p 20 A, Ap 15 A, Ap 16 A, etc. [4].…”
Section: Introductionmentioning
confidence: 99%
“…In nuclei, for microorganisms, it has been reported that poly P control gene expression [ 11 ] is a potent inhibitor of the degradosome-dependent degradation of mRNA [ 12 ] and a promoter of ribosomal [ 13 ] and nucleoid protein degradation by activating Lon protease [ 14 ]; It also assists in the fidelity of protein translation by its interaction with ribosomes [ 15 ]. In yeast, poly P interact and inhibit poly(A) polymerase activities [ 16 , 17 ]. In mammalian cells, poly P accumulates and regulates myeloma proliferation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%